A REVIEW: THIAZINES DERIVATIVES TREATED AS POTENTIAL ANTIMICROBIAL AGENTS - Sharma, Praveen Kumar; Makkar, Reena (Asian Journal of Pharmaceutical and Clinical Research, 2017)
In recent days, heterocycles and their derivatives have become strong reflection in medicinal research and pharmaceutical fields because of their practical pharmacological and biological activities. Organic compounds; mainly heterocyclic compounds are wealthy in natural world and contain extra value because their structural subunits are established in many natural products such as enzymes, vitamins, antibiotics, acids, and hormones. Thiazine nucleuses found in compounds have variety of pharmacological activities such as antitumor, antimicrobial, antibacterial, antifungal, antiviral, and anti-inflammatory. This review spotlight on the substituted thiazines with possible antimicrobial activities that are at the present in development. Keywords: Antibacterial, Substituted thiazines, Antimicrobial agents. Â